2000
DOI: 10.1046/j.1365-2389.2000.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for determining labile cadmium and zinc in soil

Abstract: Summary Isotopically exchangeable cadmium and zinc (‘E values’) were measured on soils historically contaminated by sewage sludge and ones on zinc‐rich mine spoil. The E‐value assay involves determining the distribution of an added metal isotope, e.g. 109Cd, between the solid and solution phases of a soil suspension. The E values for both metals were found to be robust to changes in the position of the metal solid⇔solution equilibrium, even though the concentration of dissolved metal varied substantially with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 18 publications
8
128
0
Order By: Relevance
“…5 Results demonstrated that neither background equilibrating extractant was uniquely suitable for the analysis of Pb, Zn and Cd for all samples.…”
Section: E-values -Methods Validation and Comparison Of Suspending Elementioning
confidence: 95%
See 4 more Smart Citations
“…5 Results demonstrated that neither background equilibrating extractant was uniquely suitable for the analysis of Pb, Zn and Cd for all samples.…”
Section: E-values -Methods Validation and Comparison Of Suspending Elementioning
confidence: 95%
“…The calibration and quality control standards were inserted every 20 samples to check possible drift over the run. Data were corrected for blank contribution and possible 5 interferences by running a number of blanks and synthetic chemical solutions of Ba, Ce, Gd, Nd, Pb and Sm. Iron concentrations in the Fe-oxide extracts was analysed by ICP-OES (Perkin Elmer Optima 7300DU).…”
Section: Analytical Procedures -Element Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations